Witsuwit’en English: language shift and First Nations English in Canada - Kinsey, Sonya (2024)
Witsuwit’en English is a variety of First Nations English (FNE) spoken by the Witsuwit’en people, in several small communities in Northern British Columbia. Despite being widely spoken, FNEs in Canada remain understudied and undervalued, often dismissed as learner Englishes, or assumed to be the result of creolization. Very few varieties have been given in-depth analysis and the state of the research in Canada lags far behind that of the USA and Australia. This book aims to provide a first and comprehensive account of Witsuwit’en English (WitEng). It starts with a review of research on FNEs in Canada, and an overview of possible linguistic features before describing the historic language contact situations that led to the Witsuwit’en variety of English. It then compares the features of WitEng to those varieties of English in the EWAVE corpus and proposes a set of stages for the development of FNEs. The development of WitEng is distinguished by unique and multi-layered contact situations, distinct from those of slave plantations and trading colonies, as revealed by the intensive fieldwork with community members and an analysis of the Witsuwit’en people’s contact with Europeans. WitEng features are drawn from sources such as the Ancestral Language, settler English varieties, and French. Non-standard features are also used to different degrees, according to age and gender. Both types of features conform with other varieties of FNEs and Native American Englishes, as well as those that can be directly traced to the Ancestral Language. The findings of this book, both in terms of the history and the books, thus provide solid proof that WitEng is clearly a variety of English and not a creole and show a series of distinct stages for the development of FNEs.